Estimating the effectiveness of a hospital's interventions in India: impact of the choice of disability weights - Susmita Chatterjee; Richard A Gosselin (The World Health Organization, 2015)
AbstractObjective To calculate the effect of using two different sets of disability weights for estimates of disability-adjusted life-years (DALYs) averted by interventions delivered in one hospital in India.Methods DALYs averted by surgical and non-surgical interventions were estimated for 3445 patients who were admitted to a 106-bed private hospital in a semi-urban area of northern India in 2012-2013. Disability weights were taken from global burden of disease (GBD) studies. We used the GBD 1990 disability weights and then repeated all of our calculations using the corresponding GBD 2010 weights. DALYs averted were estimated for surgical and non-surgical interventions using disability weight, risk of death and/or disability, and effectiveness of treatment.Findings The disability weights assigned in the GBD 1990 study to the sequelae of conditions such as cataract, cancer and injuries were substantially different to those assigned in the GBD 2010 study. These differences in weights led to large differences in estimates of DALYs averted. For all surgical interventions delivered to this patient cohort, 11 517 DALYs were averted if we used the GDB 1990 weights and 9401 DALYs were averted if we used the GDB 2010 disability weights. For non-surgical interventions 5168 DALYs were averted using the GDB 1990 disability weights and 5537 DALYS were averted using the GDB 2010 disability weights.Conclusion Estimates of the effectiveness of hospital interventions depend upon the disability weighting used. Researchers and resource allocators need to be very cautious when comparing results from studies that have used different sets of disability weights.